A Survey of Mergers in the UK Legal Industry 1991-2006 - Craven, Edgar (2006)
This study is a survey of mergers in the UK legal industry between 1991 and 2006. The legal industry represents an interesting and hitherto neglected area to study. During the period of this study the industry has undergone rapid structural change with considerable consolidation between UK law firms. The legal industry also has a number of interesting features which should make the study of mergers within it particularly relevant. Law firms enjoy a monopoly over the provision of legal services in the UK, they must be formed in partnerships and they can only practice law. These distinct features of the industry make it an interesting testing ground for assessing current theories about mergers especially in light of forthcoming legislation to deregulate the industry. This study focuses particularly on four aspects of mergers: the effect of mergers on profits; the conditions leading to mergers; differences in levels of profitability between merger partners; and changes in headcount following merger.